Optimization of Prediction Intensity of Big Data Clustering Algorithm Integrated with Distributed Computing in Cloud Environment - Ji, Chunmei; Zhou, Jing; Kong, Fengbo (Informatica, 2024)
Through the existing hardware resources such as servers and storage in the data center, the use of virtualization technology to integrate hardware resources and network resources, etc., build a data center private cloud management platform, which can optimize the highly standardized servers and fully improve the hardware Resource utilization. Through a unified private cloud management platform, the rapid deployment of hardware resources can be achieved and the operability of data can be enhanced. It can meet most analysis tasks, quickly respond to analysis needs and improve the efficiency and quality of system management. Realize the rational allocation of data resources with minimal management cost and workload. During the period of continuous adjustment of the business system, the school can use the cloud data center to allocate resources according to the needs, meet the real-time deployment requirements of IT and carry out real-time risk monitoring of cloud data, identify threat programs for isolation processing and feedback and perform daily business operations Abnormalities are collected and hidden dangers are discovered and early warning is given in time. On the other hand, service providers can also develop customized security services based on the level of corporate information security requirements.